COMPUTER-BASED COGNITIVE DEVELOPMENT MODEL BY APPLYING REGGIO EMILIA APPROACH TO KINDERGARTEN CHILDREN - ., Parwoto (Program Pascasarjana Universitas Negeri Makassar, 2015)
The main problem of this research is how to model computer-based cognitive development in Reggio Emilia approach which is developed can enhance childrenâs creative thinking in school. The research method used is a research and development. Data collection methods used questionnaire, interview, observation, and documentation. The data collected was processed by descriptive qualitative with percentage techniques to examine the category level and specific dimensions of the aspects measured. The stages of development model were conducted at the level of needs assesment, content validation, and operational or empirical validation of the model. The result of the needs assessment on PKBK-REA Â model in general oriented on experience through the adoption of Microsoft paint program, Correl draw, and Adobe Photo is extremely Â needed in schools, especially for gifted education services. Therefore, it is urgent to develop a computer-based cognitive development model oriented on the development of childrens creative thinking abilities. The results of the analysis of limited test and the class test reveal that there are significant differences between the a group of children who apply the Reggio Emelia approach and a group of children who apply the conventional learning, where creativity in playing computer for children who attend computer-based cognitive development model using Reggio Emelia approach is better than the ones who attend conventional learning. PKBK-REA model and devices that have been developed are effective and efficient in the development of kindergarten childrens creativityÂ Keywords: Model, cognitive, computer, Reggio Emilia, children, kindergarden